2009
DOI: 10.1108/09600030910996251
|View full text |Cite
|
Sign up to set email alerts
|

Managing supply chains in times of crisis: a review of literature and insights

Abstract: Purpose-The purpose of this paper is to review the literature to describe the current practices and research trends in managing supply chains in crisis. This paper also provides directions for future research in supply chain crisis management. Design/methodology/approach-Articles published prior to August 2008 are analyzed and classified. Findings-A unique five-dimensional framework to classify the literature is provided. The study reveals that there has been extensive research done in this area in recent year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
193
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(207 citation statements)
references
References 92 publications
3
193
0
11
Order By: Relevance
“…Natarajarathinam et al (2009) reviewed publications pertaining to supply chain management (SCM) in times of crisis. The literature selected by the athors's focused on SCM disruptions i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Natarajarathinam et al (2009) reviewed publications pertaining to supply chain management (SCM) in times of crisis. The literature selected by the athors's focused on SCM disruptions i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of these two papers is due to the inevitable issue of subjectivity when manual scrutiny is involved in any paper review activity. (Altay and Green, 2006), (Natarajarathinam et al, 2009), and (Galindo and Batta, 2013) are papers known to have also acknowledged this issue.…”
Section: Scope Of Study and Adopted Search Methodologymentioning
confidence: 99%
“…We selected the seven literature review studies most related to disaster operations management, humanitarian logistics and transportation in humanitarian logistics, including those by Altay and Green [1], Galindo and Batta [4], Caunhye et al [5], Natarajarathinam et al [6], Apte [7], Anaya-Arenas et al [8] and de la Torre et al [9].…”
Section: Academic Studiesmentioning
confidence: 99%
“…In addition to the above three reviews focused on operations research, Natarajarathinam et al [6] focused on the supply chain management literature in emergency management. In their paper, the authors classified the literature reviewed according to the scale, stage and source of the crisis and made future research suggestions in consideration of the gaps identified.…”
Section: Academic Studiesmentioning
confidence: 99%